Match demands and perceived exertion of cerebral palsy soccer national team players - Wartner, D.; Cost, R.; Andersen, J. C.; Oliva-Lozano, J. M. (Sports Health: A Multidisciplinary Approach, 2025)
Background: The aims of this study were to analyze match demands and perceptual responses of cerebral palsy soccer national team players. Specifically, to identify whether variations in match demands exist between playing positions and between halves.